Security issues and system structure of internet of vehicles - Liang-min WANG; Ting-ting LI; Long CHEN (网络与信息安全学报)
Instead of focusing on concrete security requirements of each IOV applying scenario,the architecture characteristics of the IOV networking systems were summarized,and the main security problems were extracted by analyzing the connotation and network architecture of IOV in different development stages.Then an identity authen-tication based three-tier security architecture over the clearly analyzed concept and structure was proposed,and the related IOV security research with the view of the presented three-tier security architecture were surveyed.Finally,some new developments and progresses over security of IOV were presented.